Common Iliac Artery Thrombosis following Pelvic Surgery Resulting in Kidney Allograft Failure Successfully Treated by Percutaneous Transluminal Angioplasty with Balloon-Expandable Covered Stent. (18th August 2015) - Golla, Maheswara S.; Acharjee, Subasit; Jaber, Bertrand L.; Garcia, Lawrence A.
Abstract : We report the case of a 66-year-old woman who developed acute kidney allograft failure due to thrombotic occlusion of the common iliac artery after hysterectomy requiring emergent allograft rescue. She underwent percutaneous transluminal angioplasty with endovascular balloon expandable covered stent graft placement in the right common iliac artery. Although there are a handful of case reports of acute limb ischemia secondary to acute common iliac artery thrombosis, this is the first case reported in the literature resulting in successful kidney allograft rescue following pelvic surgery.